2008
DOI: 10.1177/112067210801800101
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors and Binocular Dysfunctions in a Population of University Students

Abstract: High near visual demand could be the most important factor for higher incidence of myopia, worse convergence and fusion amplitude, higher degree of exophoria, and worse results in Titmus test in the student population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…In other cases, Germany, the USA, the UK, including Northern Ireland, Greece, Spain, Chile, Bulgaria, Thailand, Brazil, Jordan, Indonesia, Argentina, Portugal, in Moravia, now part of the Czech Republic, Turkey, the Russian Federation, Serbia, Romania and Tunisia, there is some information which enables them to be classified as locations with a low prevalence of myopia, although the evidence is not always strong, due to often severe limitations in study methodology. Israel provides an important set of data, because while the prevalence of myopia in the general population is in the low range, the prevalence is very high in boys, but not girls, studying in Orthodox and ultra‐Orthodox schools with very heavy educational loads …”
Section: Resultsmentioning
confidence: 99%
“…In other cases, Germany, the USA, the UK, including Northern Ireland, Greece, Spain, Chile, Bulgaria, Thailand, Brazil, Jordan, Indonesia, Argentina, Portugal, in Moravia, now part of the Czech Republic, Turkey, the Russian Federation, Serbia, Romania and Tunisia, there is some information which enables them to be classified as locations with a low prevalence of myopia, although the evidence is not always strong, due to often severe limitations in study methodology. Israel provides an important set of data, because while the prevalence of myopia in the general population is in the low range, the prevalence is very high in boys, but not girls, studying in Orthodox and ultra‐Orthodox schools with very heavy educational loads …”
Section: Resultsmentioning
confidence: 99%
“…15 More than half of our study participants experienced the visual problems like ametropia which has proven by past studies where visual refractive errors are more common in pathologists than in the general population, university students or other hospital workers. [16][17][18][19][20][21] It is possible that ametropic students may choose more likely to enter this discipline. On the other hand, the work of pathologists is associated with possibly eye-straining activities such as long-lasting microscopy and computer work.…”
Section: Discussionmentioning
confidence: 99%
“…Korniushina conducted a study on microscope users, subjects working with magnifying glasses, and computer users and found that the highest overstrain was observed after 4 years of work in microscope operators who might develop professional myopia due to deprivation of accommodation [16]. A clinical study by Risovic et al, to determine the presence of refractive errors and binocular dysfunction in a population of university students with heavy near visual demands found it to be the most important factor for higher incidence of myopia, worse convergence, and exophoria [17]. The limitation of our study was that the other factors like long hours of computer work and the possibility of ametropic students entering these professions in greater numbers could not be ruled out.…”
Section: Resultsmentioning
confidence: 99%